Sources of risk in commercial banks: conventional vs Islamic banks - Tafri, Fauziah Hanim; Abdul Rahman, Rashidah; Hamid, Zarinah (British Academic Journal, 2012)
The focus of this study is to identify the level of seriousness of the sources of major risks faced by Islamic and conventional banks in Malaysia and selected Islamic Banks outside Malaysia. Furthermore, the study seeks to identify the risks that potentially threaten the bank’s market value. The study employs a survey questionnaire distributed to banks in Malaysia and outside Malaysia, which includes conventional banks (referred to as type “conventional bank 1”), conventional banks with Islamic banking schemes in operation (referred to as type “conventional bank 2”) and full-fledged Islamic banks. The results showed that the level of seriousness of the sources of major risks faced by the Islamic banks is the same as the conventional banks and that there is no significant difference in the level of concern of risks between the two types of bank.